Types of the maxillary labial frenulum and median diastema in children: A cross-sectional study (Annals of Medical Research, 2025)
Aim: The aim of this study is to determine the frequency of different types of maxillary labial frenulum in children aged 4-13 years and whether they have an effect on median diastema.Materials and Methods:  This study is a cross-sectional study conducted on 723 children aged 4-13 years who applied to the Department of Pedodontics, Faculty of Dentistry, Inonu University for examination. The examination of the children participating in the study was performed by sitting them upright under normal light. The patient's frenulum type was determined by performing the blanch test. The diastema between the maxillary central teeth was measured with an orthodontic caliper and  was recorded.Results: The data were analyzed descriptively and analytically. 343 boys and 380 girls were examined in this study. The most common maxillary labial frenulum type in the examined children was found to be the gingival frenulum type (57%), and the least common maxillary labial frenulum type was the papillary penetrating frenulum type (2%). When we looked at the amount of diastema in our study, the median diastema was mostly between 0-2 mm in the primary dentition, while the median diastema was mostly not seen in the mixed and permanent dentition.Conclusion: As a result, it was seen that there was a significant relationship between frenulum type and median diastema, but there was no significant relationship between gender and frenulum type.
Keywords: Median diastema; Maxillary labial frenulum; Children